2004
DOI: 10.1590/s1516-35982004000300026
|View full text |Cite
|
Sign up to set email alerts
|

Exigências nutricionais de zebuínos: minerais

Abstract: Com o objetivo de determinar as exigências dos macroelementos minerais (Ca, P, Mg, K e Na) de zebuínos, foi conduzido um experimento no Departamento de Zootecnia da Universidade Federal de Viçosa, utilizando-se 16 novilhos castrados, com peso vivo médio inicial de 270 kg, mantidos em confinamento. Quatro animais foram abatidos, após o período de adaptação, para servirem como referência, e os doze restantes foram distribuídos em três tratamentos com diferentes níveis de concentrado nas dietas (5, 35 e 65%), na … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…Such value is found close to the one recommended by NRC (2000) (EBWG) in requirements for live weight gain (LWG), i.e., the requirements supplied in function of empty body weight gain have to be multiplied by 0.9013 to find the requirements in function of live weight gain. Paulino et al (2004) found the relationship between EBWG and LBW of 0.900, close to the one presented in this study. NRC (2000) used the relationship 0.956 between EBWG and LBW.…”
Section: Resultssupporting
confidence: 90%
“…Such value is found close to the one recommended by NRC (2000) (EBWG) in requirements for live weight gain (LWG), i.e., the requirements supplied in function of empty body weight gain have to be multiplied by 0.9013 to find the requirements in function of live weight gain. Paulino et al (2004) found the relationship between EBWG and LBW of 0.900, close to the one presented in this study. NRC (2000) used the relationship 0.956 between EBWG and LBW.…”
Section: Resultssupporting
confidence: 90%
“…As animals were aging, rates of deposition of macromineral reduce inasmuch as most of the mineral content, 99, 80 and 70% of Ca, P and Mg, respectively, are found in the bone tissue (AFRC, 1991; Coelho da Silva, 1995;NRC, 2000). However, K and Na are present mainly in the intra and extracellular fluids, respectively (Paulino et al, 2006b).…”
Section: Resultsmentioning
confidence: 99%